The Doctrine of the Devil in the Midst of Feudalism: A Literary Sociology of Reymond William in Serat Jiljalaha - Maulana Nurul Izza (Javanologi: International Journal of Javanese Studies, 2026)
Serat Jiljalaha is one of the anomalous Serats written in the 19th-century Javanese script. Using the form of tembang macapat from pupuh Dhandhanggula to pupuh Mijil, which presents the figure of Kyai Jajalanat (King of Satan) from Mount Candisewu, issuing immoral warnings ranging from usury, adultery, opium, gambling, to robbery. Through the aesthetic strategy of value reversal and religious parody, Jiljalaha became a sharp social critique of the colonial feudal situation at that time. When priyayi, ulama, and colonial governments appear as moral representations, in practice, they reproduce structural violence, exploitation, and immoral behaviour. With the approach of literary sociology, Raymond William, this study reads the Serat Jiljalaha as a dominant, residual and emergent cultural. Two main questions guide this analysis: how does the Jiljalaha represent and critique the dominant culture of religious morality, and how are traces of pre-Islamic Javanese residual culture and satirical elements as emergent culture used to dismantle the contradictions that dominate society at that time?. The results of the reading show that Jiljalaha is not only a parody, but also presents a form of symbolic resistance in which this Serat displays its opposite as a method of criticism. This text reveals how colonial power created performative morality while society experienced a deep crisis of ethical orientation. Serat jiljalaha captures the structure of feeling of 19th-century Javanese society, which is ambivalent towards the order that is collapsing but has not found a replacement. Through sociological readings, Serat Jiljalaha appear as a counterlesson to the Serat of teaching in general.